Chão de vidas, rios de memórias: histórias indígenas do Amazonas Imperial 1845-1888 - Braga, Bruno Miranda (2022)
The thesis presents aspects of the indigenous daily life of the Amazon in the 19th century, specifically in the Second Empire between 1845-1888. At that time, Brazil on the guise of D. Pedro II was on the indigenistic policy of catechese and civilization of the Indians, which was an instrument based on indigenistic laws of colonial periods, bringing back the system of villages. For the Amazon a series of events mark this moment especially moments involving indigenous peoples, their struggles, trajectories, and daily reinventions. Each group of the Indigenous Amazon that inhabited the hileia in those years had motivations, aspirations, emotions that drove their action and their actions. Baré, Wapixana, Werekena, Tariana, Mayoruna, Cobéu, Miranha, among others are the central actors of this text and all the plot that his performance and protagonism engendered in the daily life of the 18th century Amazon, in this I broke with the mistaken idea of "generic Indian", but it was possible to identify peculiarities, anides and struggles of different groups. The perspective of documentary analysis was the New Cultural History taking the subjects as holders of culture, emotions that acted driven by reasons that were their own, not only imposed. I worked with a wide set of documents from reports of provincial presidents to photographs in which I found the actions of different indigenous groups and tried to emphasize their ways of living in the midst of the hostile provincial period